Biodegradable Wet Wipes dari Sabut Kelapa Sawit (Palm Fiber) dengan Ekstrak Flavonoid Daun Kelapa Sawit Sebagai Bahan Antibakteri - Fadilah, Fadilah; Ningtyas, Divanda Sekar Rahayu; Dewi, Audrey Vista Candra; Krisnawati, Anita Budi; Putra, Reyza Fachrezy (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
The wet tissue currently circulating in the market is made of synthetic fibers consisting of 30% viscose fibers and 70% polyester fibers, and 90% of the wet tissue contains plastic. Indonesia's palm oil industry grows annually, however. Palm fiber waste has high cellulose, useful as wet tissue raw material substitute. This study used flavonoids from palm leaves as an antibacterial material to create biodegradable wet wipes from palm fiber and evaluate their antibacterial and antiseptic effectiveness. The best characteristics of biodegradable wet wipes are obtained with a composition of 91.5% (w/w) palm coconut fiber cellulose, and a ratio (w/w) of PVA:tapioca:chitosan at every 10 mL of used VCO of 2:3:6 (1.5%:2.25%:4.5%) with variations in pulp bleaching and the method of applying the binder solution by being spread onto semi-dry tissue paper. The evaluation of wet tissue includes tests for tensile strength, color, biodegradability, phytochemical analysis, antibacterial testing, antiseptic testing, irritation testing, and pH testing. The test results showed that biodegradable wet wipes made of palm coconut fiber and flavonoid extract from palm coconut leaf at concentrations of 10%, 15%, and 20%, which have been adjusted to SNI 8526:2018 standard, have bacterial reduction effectiveness of 68.09%, 79.06%, and 89.94%, respectively.